Rapid microbial responses to temperature changes in Arctic anoxic peat soil - Bjørdal, Yngvild (UiT Norges arktiske universitet, 2021)
Arctic peatlands act as important sources and sinks of carbon. Microbial decomposition takes place in these soils, producing the greenhouse gasses carbon dioxide and methane as end-products. A variety of aerobic and anaerobic microbial pathways are involved in the decomposition of organic material in peat soil. In anoxic soil layers, methane and carbon dioxide is often produced through syntropic partnerships between several fermenters and methanogens. Changes in soil conditions like temperature and substrate availability affect which methanogenic and fermentative pathways are dominant in the soil, thus affecting the final gas emissions. Due to their size and fast metabolism, microorganisms have the potential to respond rapidly to environmental changes like temperature variation and are constantly exposed to short-time temperature changes on daily and hourly basis in many natural and anthropogenic ecosystems. How short-term temperature variation affect soil microbial communities is yet poorly understood. In this master thesis I have investigated microbial responses in Arctic peat soil to temperature changes (heating and cooling). A high resolution 9-week incubation experiment with temperature increase from 2 – 10°C followed by cooling from 10 – 2°C was carried out, thus exposing the peat soil to a temperature range and timeframe similar to Arctic summer season temperature shifts. Gas and metabolite accumulation and microbial community growth and biomass was monitored to establish knowledge about the effects. Methane accumulation was rapidly affected by heating and showed increasing accumulation rates at warmer temperatures. However, exposure to cooling did not immediately reduce the accumulation of methane. This delay might be an effect of established high growth rates at higher temperatures that takes longer time to reverse. A change from no net carbon dioxide emission below 6°C to emission rates increasing rapidly due to heating above 6°C was observed. This change occurred at the same time and temperature as ...